Trinidad and Tobago. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Trinidad and Tobago during 2014 are identified, with regard to the needs and interests of the country, strengthening on topics such as health, innovation, technology, methodology, trade, women’s inclusion and in production tubers, cassava, honey, fruits, goats and milk.